A Copper‐Catalyzed Synthesis of Pyrroles through Photochemically Generated Acylazirines. Issue 42 (31st October 2019) - Paternoga, Jan; Opatz, Till
Abstract : A synthesis of highly substituted 2, 4‐diacylpyrroles through a Cu‐catalyzed dimerization of acylazirines generated in situ by a photochemical valence isomerization is described. The shown methodology allows the use of simple precursors and a readily available copper(II)‐catalyst. Since the reaction is best performed at elevated temperatures, a method to adjust the temperature of the reaction mixture during this dual light and metal‐induced process was established. Additionally, mechanistic studies of the reaction were performed in order to provide a deeper understanding of the chemistry of 2‐acylazirines. Abstract : A protocol for the synthesis of highly substituted 2, 4‐diacypryrroles via a copper‐catalyzed ring strain releasing dimerization reaction was developed. The pyrroles are synthesized combining UV–photochemistry and metal‐catalyzed follow up reaction in an one‐pot system. To match the rates of the thermal and the photoinduced step, an internal temperature control was established.